Analisis Efektivitas Live Streaming “PVN Shoes” pada E-Commerce - Prakasta Karisma Putra; Terrylina Arvinta Monoarfa; Meta Bara Berutu (Journal of Business Application, 2025)
This study aims to evaluate the effectiveness of "PVN Shoes" live streaming on the Shopee E-Commerce platform using the Stimulus-Organism-Response (SOR) framework. The descriptive analysis indicates that the E-Commerce Anchor Attribute dimension demonstrates a high level of effectiveness. The host plays a crucial role in enhancing audience interaction and influencing purchasing decisions, as viewers tend to feel more confident and emotionally connected to the promoted products. Similarly, the Immersion dimension reveals a significant positive impact, where audience engagement and deep experiential involvement contribute to a more enjoyable and interactive viewing experience. This fosters a stronger connection between the viewers and the products, encouraging active participation during live sessions. Moreover, the Perceived Scarcity dimension also shows high effectiveness, with the perception of limited product availability triggering a sense of urgency and competitive behavior among viewers. This psychological response stimulates quicker purchasing decisions and heightens consumer enthusiasm for PVN Shoes. Overall, the study concludes that the three dimensions Anchor Attribute, Immersion, and Perceived Scarcity elicit effective audience responses to PVN Shoes’ live streaming events. However, several aspects within each dimension require further improvement to enhance the overall audience experience and increase both interaction quality and purchase conversion rates.